PENGARUH PEMBERIAN TOMAT CERI TERHADAP VOLUME SALIVA DAN LAJU ALIR SALIVA PADA LANSIA DI WREDA KARITAS - Thoharoh, Siti; Laela, Dewi Sodja; Nurjanah, Neneng; Octaviana, Devy (Jurnal Terapi Gigi dan Mulut, 2024)
With increasing age, the function of the body's organs will decrease both due to natural factors and due to disease. One of the things related to the deterioration of the oral cavity is the production of salivary glands. Tomato fruit (Solanum Lycopersicum L.) contains vitamins and compounds that are good for health, especially Lycopene. The purpose of this study was to determine the volume of saliva before and after consuming cherry tomatoes, and to determine the saliva flow rate before and after consuming cherry tomatoes in the elderly at the Karitas Cibeber Nursing Home. Pre-experiment research type with One Group Pretest Posttest design, population of 26 respondents and purposive sampling technique. The research was conducted in February 2024. Analysis using the Wilcoxon test. The results showed that the average salivary volume before consumption of cherry tomatoes was 0.565 cc and after consumption of cherry tomatoes was 0.915cc. Salivary flow rate before consumption of cherry tomatoes 1.24 minutes and after consumption of cherry tomatoes 0.79 seconds. There is a significant effect between the consumption of cherry tomatoes on the volume and flow rate of saliva (p <0.05).